2006
DOI: 10.1111/j.1748-7692.2006.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

FOOD AND FEEDING ECOLOGY OF THE COMMON DOLPHIN (DELPHINUS DELPHIS) IN THE OCEANIC NORTHEAST ATLANTIC AND COMPARISON WITH ITS DIET IN NERITIC AREAS

Abstract: The short‐beaked common dolphin, Delphinus delphis, is abundant in both neritic and oceanic habitats. These two domains differ largely in terms of the nature of forage organisms and their availability to surface‐bound top predators, which suggests that the common dolphin should show extensive variability in foraging strategies as a response to these different habitats. However, although its diet is well known over continental shelves, so far, mostly because of sampling issues, nothing has been published on its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 28 publications
1
76
0
Order By: Relevance
“…This sampling made use of fish and squid collected during trawling surveys, as well as market sampling, or material collected for other projects. Selection of species was based on identification of the main prey species from the literature (Santos and Pierce, 2003;Santos et al, 2004aSantos et al, ,b, 2005De Pierrepont et al, 2005;Pusineri et al, 2007) and unpublished data held by the authors, although minor prey species were also included where material was available. Variation in contaminant concentrations in prey tissues was analysed in relation to taxonomic group, geographical location and body size.…”
Section: Sampling Programmementioning
confidence: 99%
“…This sampling made use of fish and squid collected during trawling surveys, as well as market sampling, or material collected for other projects. Selection of species was based on identification of the main prey species from the literature (Santos and Pierce, 2003;Santos et al, 2004aSantos et al, ,b, 2005De Pierrepont et al, 2005;Pusineri et al, 2007) and unpublished data held by the authors, although minor prey species were also included where material was available. Variation in contaminant concentrations in prey tissues was analysed in relation to taxonomic group, geographical location and body size.…”
Section: Sampling Programmementioning
confidence: 99%
“…Sardine and horse mackerel were found to be the most important prey eaten with the blue whiting in Galicia (Santos et al 2004a), and off Portugal, Silva (1999) found that the most common prey of common dolphins were sardine 284 and blue whiting, known as common species in local waters. Finally, in the oceanic area off the Bay of Biscay, common dolphins fed mainly on myctophids, mostly Notoscopelus kroeyeri, and oceanic cephalopods like Teuthowenia megalops and Gonatus steenstrupi (Pusineri et al 2007). The prey species assemblages observed in these oceanic common dolphins and the nearby neritic ones (present study) are thus completely different, reflecting the locally most abundant prey type.…”
Section: Overall Diet Of Common Dolphinsmentioning
confidence: 99%
“…To minimize overestimation of the relative importance of prey whose remains are resistant to digestion, each prey item was scored on a scale according to its degree of digestion. This allowed us to determine a fresh fraction that would better represent the composition of the ingested prey than a total diet composition derived from all prey items (Pusineri et al 2007). The number of individuals was determined as half the number of otoliths rounded up to the integer for fish and as the maximum number of lower or upper beaks for cephalopods (Pierce & Boyle 1991).…”
Section: Samplingmentioning
confidence: 99%
“…Common dolphin distribution in the region is also known to vary on seasonal and inter-annual time scales, likely related to shifting prey distributions and oceano graphic conditions (Campbell et al 2015). Opportunistic feeding behavior of common dolphins ob served around the world suggests that their diet represents prey that are locally available and energy-rich (Silva 1999, Pusineri et al 2007, Meynier et al 2008, Spitz et al 2010. Therefore, the foraging behavior of common dolphins may indicate the distribution and relative abundance of dolphin prey.…”
Section: Introductionmentioning
confidence: 99%